Low Temperature Deposition of Highly Cyclable Porous Prussian Blue Cathode for Lithium‐Ion Microbattery. Issue 25 (24th May 2021) - Patnaik, Sai Gourang; Pech, David
Abstract: Small dimension Li‐ion microbatteries are of great interest for embedded microsystems and on‐chip electronics. However, the deposition of fully crystallized cathode thin film generally requires high temperature synthesis or annealing, incompatible with microfabrication processes of integrated Si devices. In this work, a low temperature deposition process of a porous Prussian blue‐based cathode on Si wafers is reported. The active material is electrodeposited under aqueous conditions using a pulsed deposition protocol on a porous dendritic metallic current collector that ensures good electronic conductivity of the composite. The high voltage cathodes exhibit a huge areal capacity of ≈650 μAh cm −2 and are able to withstand more than 2000 cycles at 0.25 mA cm −2 rate. The application of these electrode composites with porous Sn based alloying anodes is also demonstrated for the first time in full cell configuration, with high areal energy of 3.1 J cm −2 and more than 95% reversible capacity. This outstanding performance can be attributed to uniform deposition of Prussian blue materials on conductive matrix, which maintains electronic conductivity while simultaneously providing mechanical integrity to the electrode. This finding opens new horizons in the monolithic integration of energy storage components compatible with the semiconductor industry for self‐powered microsystems. Abstract : Utility of nanoporous metallic current collectors for microenergy storage devices with high areal capacity is exhibited with electrodeposited Prussian blue cathodes and Sn based anodes. Ultrathin porous films are fabricated on Si wafers followed by conformal deposition of active materials through simple non‐vacuum technology. Full Li ion microbattery having excellent performance metrics and industrial promise is showcased.